Influence of loads to the joint moments and mucle force repartition in sprint cycling test - Benkhemis, I.; Boucher, M. (ISB Congress, 2006)
The aim of this preliminary study is to compare the muscular force optained when using the physiological cross-section area (PCSA) during a sprint test performed by a road and a track cyclist.